Pengembangan Potensi Wisata Desa Senaru Melalui Berbagai Kegiatan Optimalisasi Wisata Bersama Kuliah Kerja Nyata Universitas Mataram - Ni Wayan Sri Suliartini; Pande Komang Suparyana; Maiser Syahputra; Abdul Muta Alli Anwar; Ahman Alfan Ansori; Dano Syahputra; Ihsan Itqanul Amal; Sarah Lehani Mitchell (Universitas Mataram, 2023)
Senaru Village is a tourist village that has several tourism potentials. This tourism potential needs to be developed to increase the number of tourists to the area. This activity aims to develop tourism potential in Senaru Village through various work programs at the University of Mataram. The activity was carried out from 24 November 2022 until 10 February 2023 at several locations in Senaru Village. Tourism potential development activities in Senaru Village are carried out in several stages of activity, namely debriefing, surveys, preparation of work programs and implementation of work programs. The work program implemented consists of making information boards in coffee plantations including determining the design for information boards, determining the location of information boards, selecting materials, making information boards, and placing information boards in predetermined locations; Making promotional videos of coffee plantations, waterfalls, river tubing and traditional houses including: determining the concept of a promotional video, surveying locations for making videos, shooting videos, editing videos; Tourism awareness village outreach includes preparatory activities, socialization at the village office, and discussion sessions. Activities to clean tourist attractions in Senaru Village are carried out in mutual cooperation with youth, Pokdarwis and the community to clean waterfall tourist attractions every Sunday; Making trash cans from ecobrick includes the following activity stages: collecting materials, making trash cans from ecobrick, and placing ecobrick trash cans in a predetermined location. The results of the activities are in the form of information boards that are installed at tourist sites and prayer rooms, virtual guiding videos, increasing public understanding of tourist villages and disaster mitigation at tourist sites and ecobrick bins. The conclusion that can be drawn is that all activities have been carried out and run smoothly.